The Interdependence of Competition Policy, Consumer Policy and Regulation in Introducing and Safeguarding Effective Competition in the EU Telecommunications Market - Andreas Bartels; Doru Alexandru Pleșea; Michael Studeny; Vanessa Just (Amfiteatru Economic Journal, 2017)
Currently, the European Union finds itself in troubled waters. It has to prove that its benefits outweigh the costs of its endeavour. In this respect, an EU competition policy that focuses on consumer welfare is one way to gain support by the citizens of its member states. The Roaming Regulation that has reduced the mobile communications costs while travelling abroad serves as a good example for this approach. The EU Commission views consumer policy as another important factor to protect and benefit customers. In markets with natural monopolies, the two policies require the support of an effective regulatory policy. The research demonstrates that these three policies – if harmonised – are able to lead to an increase in consumer welfare (primarily by reducing prices) and that they protect the rights and interests of consumers. In the case of telecommunications, several initiatives of the European Commission and of national regulatory authorities to falls in prices and forced operators to implement customer friendly rules and to protect customer data and privacy. The authors consider that the European Commission has tried to establish and harmonise rules across all member states in order to protect the interests and rights of consumers on the telecommunication market. The enforcement of competition and consumer policy within institutions from the telecom field certainly could promote the focus on consumers and the possibility to use a large “toolbox”. Harmonising and adjusting the policies across different countries and institutions and minimising any possible side effects is nevertheless a challenging task for the EU Commission in the future.
Keywords: D18; D40; K20; L96; 330; Competition policy; consumer policy; regulation; European Union; telecommunications